Constraints on the chemical enrichment history of the Perseus Cluster of galaxies from high-resolution X-ray spectroscopy. Issue 2 (29th November 2018) - Simionescu, A; Nakashima, S; Yamaguchi, H; Matsushita, K; Mernier, F; Werner, N; Tamura, T; Nomoto, K; de Plaa, J; Leung, S-C; Bamba, A; Bulbul, E; et al.
Abstract: High-resolution spectroscopy of the core of the Perseus Cluster of galaxies, using the Hitomi satellite above 2 keV and the XMM–Newton Reflection Grating Spectrometer at lower energies, provides reliable constraints on the abundances of O, Ne, Mg, Si, S, Ar, Ca, Cr, Mn, Fe, and Ni. Accounting for all known systematic uncertainties, the Ar/Fe, Ca/Fe, and Ni/Fe ratios are determined with a remarkable precision of less than 10 per cent, while the constraints on Si/Fe, S/Fe, and Cr/Fe are at the 15 per cent level, and Mn/Fe is measured with a 20 per cent uncertainty. The average biases in determining the chemical composition using archival CCD spectra from XMM–Newton and Suzaku typically range from 15 to 40 per cent. A simple model in which the enrichment pattern in the Perseus Cluster core and the protosolar nebula are identical gives a surprisingly good description of the high-resolution X-ray spectroscopy results, with χ 2 = 10.7 for 10 degrees of freedom. However, this pattern is challenging to reproduce with linear combinations of existing supernova nucleosynthesis calculations, particularly given the precise measurements of intermediate α-elements enabled by Hitomi . We discuss in detail the degeneracies between various supernova progenitor models and explosion mechanisms, and the remaining uncertainties in these theoretical models. We suggest that including neutrino physics in the core-collapse supernova yield calculations may improve the agreement with the observed pattern of α-elements in the Perseus Cluster core. Our results provide a complementary benchmark for testing future nucleosynthesis calculations required to understand the origin of chemical elements.